(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
This paper explores the issues and circumstances that come to play when good governance plays a role in determining the success of the fiscal policy. It shows that, despite its ability to improve the capacity of a given country to make counter cyclical fiscal policies, good governance does not directly increase the chances that a recession will occur. This is due to the absence of a systematic connection between the quality of governance and the risk of recession, which suggests that governance is a necessary, but not sufficient, factor in the successful fiscal intervention. Empirical findings also indicate that good governance principles are one of the limited factors that are always coupled with successful counter cyclical fiscal capacity. The connection between the quality of governance and the effectiveness of fiscal policy is demonstrated to be two way and it is dependent on the economic cycle. The presence of strong institutions, which are typified by transparency, accountability and procedural capacity enhances the transmission mechanisms of fiscal policies. However, fiscal effectiveness can be limited even in well-managed nations when recessions are taking place and the fiscal spending has a low demand-creating power. There is another set of complexity in implementing the fiscal policy, which is political-economic constraints. These nations that have poor governance are characterised by higher shadow economy and poor fiscal performance. A quality of governance is determined as a crucial factor of the foreign direct investment inflows and the growth implications. Though the developed economies have increasingly become more fiscal responsive, they have not been the same in the low-governance situations. Transparency and accountability are inalienable in boosting fiscal credibility and performance, access to information on income and assets of the public officials strengthens public checks. In this paper highlights governance reform as the foundations of sustainability and effectiveness of the fiscal policy.